Scalability implications of virtual private networks. - De Clercq, J.
This article gives an overview of the most promising technologies for service providers to offer virtual private network services. The focus is on the analysis of the scalability implications of these virtual private network mechanisms on existing service provider backbone networks. Very often, when deploying VPN services, service providers will be confronted with a trade-off between scalability and security. VPNs that require site-to-site interconnectivity without strong (cryptographic) security can be deployed in a scalable way based on the network-based VPN model, as long as the interaction between the customer and provider routing dynamics are controlled. VPNs that require strong (end-to-end) cryptographic security should be deployed according to the CPE-based VPN model, using the available IPsec protocol suite
Keywords: CPE-based VPN model; IPsee protocol suite; VPN services; Backbone networks; Cryptographic security; Network security; Network-based VPN model; Routing dynamics; Service providers; Virtual private network services; Virtual private networks scalability